(untitled) (Global Journal of Medical Research, 2020)
OSA is considered as an independent risk factor for cardiovascular morbidity and mortality. Hypertension, atrial fibrillation, heart failure with reduced ejection fraction, stroke and metabolic syndrome are also known to be associated with OSA. Each of these conditions are associated with 2D-ECHO abnormalities and often present with increased hospitalization rates or morbidity. However, echocardiographic parameters in newly detected OSA, without any other associated illness, is poorly defined. The aim of this study is to evaluate systolic and diastolic dysfunction using 2D speckle tracking in patients with newly diagnosed OSA and normal left ventricle ejection fraction. The association between diastolic dysfunction, Global Longitudinal Strain (GLS), LV hypertrophy, LV mass, estimated pulmonary artery pressures and severity of OSA was also studied. The results indicated that most of the patients with OSA, without any other cardiovascular diseases, exhibited normal left ventricular (LV) ejection fraction (EF), but had clinical signs and symptoms of LV systolic dysfunction.